2005
DOI: 10.1111/j.1365-2133.2005.07023.x
|View full text |Cite
|
Sign up to set email alerts
|

The CD40/CD40 ligand system is expressed in the cutaneous lesions of erythema multiforme and Stevens-Johnson syndrome/toxic epidermal necrolysis spectrum

Abstract: Activated T lymphocytes and macrophages, but also neutrophils, are presumably the main triggers of mucocutaneous damage in the SJS/TEN disease spectrum. The Fas/FasL system is significantly expressed in SJS/TEN lesions, but not in EM, where this apoptotic pathway presumably does not play a pivotal role in the epidermal damage. We suggest that the CD40/CD40L system may represent an important pathway of induction of SJS/TEN lesions, while in EM it would contribute to the immunoinflammation only as a second-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 40 publications
5
51
1
1
Order By: Relevance
“…By contrast, the role of macrophages is generally neglected. However, the present study confirms previous findings [12,13] showing that CD68+ macrophages are numerous in most TEN blisters. Their number was not correlated to the timing of the skin biopsies since they were sometimes more numerous in early than in late biopsies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…By contrast, the role of macrophages is generally neglected. However, the present study confirms previous findings [12,13] showing that CD68+ macrophages are numerous in most TEN blisters. Their number was not correlated to the timing of the skin biopsies since they were sometimes more numerous in early than in late biopsies.…”
Section: Discussionsupporting
confidence: 82%
“…Compared to T lymphocytes, the role of macrophages in TEN epidermal destruction has rarely been emphasized [12,13]. In the present study, we show using dual immunohistochemistry that macrophages are the main producers of the strong oxidative enzyme MPO in TEN skin.…”
Section: Introductionmentioning
confidence: 60%
“…IL-12 is a key cytokine of cell-mediated immune responses, released predominantly by antigen presenting cells able to induce a potent promotion of IFN-γ production by T and NK cells, enhancement of antigen-specific T-cell proliferation and differentiation of naive T cells toward the Th1 phenotype [35]. The IL-12 overexpression could be related to the enhanced expression of the CD40/CD40 ligand system recently demonstrated by our group in the cutaneous lesions [36] and sera [37] of EM and SJS/TEN patients. Indeed, previous in vitro studies demonstrated that the ligation between cell-surface CD40 and its ligand CD154 on T cells enhances the synthesis of IL-12 [38], which, in turn, up-regulates the CD154 expression on T helper cells [39], thus indicating the presence of a positive feedback loop between these cells.…”
Section: Discussionmentioning
confidence: 99%
“…These presentations differ from erythematous multiforme majus (EMM) which is related to infection and features only target-like exanthemas. SJS/TEN (denotes both SJS and TEN) and EMM are currently considered as cell-mediated reactions aimed at the destruction of keratinocytes expressing drug-related or herpes-related antigens, respectively [6]. Besides, more than 65% of SJS/TEN cases are induced by drugs including antibiotics, nonsteroid anti-inflammatory drugs (NSAIDs) and anticonvulsants [5].…”
Section: Introductionmentioning
confidence: 99%